'You Feel It in Your Body': How Australian Children and Young People Think about and Experience Feeling and Being Safe. (14th September 2016) - Moore, Tim; McArthur, Morag
Abstract : In 2012, the Australian Government announced the establishment of a Royal Commission into Institutional Responses to Child Sexual Abuse. The aim of the Royal Commission is to understand how and why sexual abuse occurred within Australian institutions and to provide guidance as to how future abuse might be prevented. The Royal Commission commissioned a mixed methods study to explore what children need to be safe and to feel safe, to explore how they determine their level of safety, and their observations about how institutions act to prevent and respond to safety issues. This article reports on the findings from the first phase of the study that involved focus groups carried out with children aged 4–17 years from different types of institutions. The discussion focused particularly on how children conceptualise safety and how they make judgments about their levels of safety. Children and young people's conceptualisation of safety had multiple dimensions, which include the idea that being safe and feeling safe are two distinct, interrelated but sometimes non‐concurrent experiences; that safety is identified and experienced as a set of feelings; trusting relationships are the foundation of safety; familiarity helps children feel safe; and safe environments are those that are ordered and orderly.